Cognitive Processing and Neurodevelopmental Perspectives on Misconceptions in Elementary Science Education: A Comprehensive Analysis - Muhammad Rusli; Mochamad Nursalim; Diana Rahmasari; Rafika Putri; Mahardika Darmawan Kusuma Wardana; Ria Alfian Rizkya Putri; Nurul Mahruzah Yulia (Postgraduate, University of Mataram, 2025)
Misconceptions in elementary science education are a persistent challenge embedded in the cognitive architecture and neurodevelopmental trajectories of young learners. This comprehensive analysis examines the phenomenon of science misconceptions in elementary school students through the integrated lens of cognitive processing theory and brain development research. By synthesizing contemporary neuroscience findings with an established cognitive psychology framework, this article elucidates the neurobiological underpinnings of misconception formation, persistence, and potential remediation strategies. The analysis reveals that misconceptions are not simply learning errors but, rather, systematic constructs arising from the interaction of developing neural networks, limited cognitive resources, and intuitive reasoning patterns. Limited prefrontal cortex maturity, working memory constraints, and a tendency toward intuitive thinking create a developmental context in which misconceptions naturally emerge. Next, the article explores how neurodevelopmental factors (such as synaptic pruning and executive function development) influence the process of conceptual change. By testing various theoretical frameworks, including conceptual change theory and the dual-process model of cognition, in a neurodevelopmental context, this work provides educators and researchers with a deeper understanding of why misconceptions persist and how evidence-based instructional strategies aligned with brain development can facilitate more effective conceptual understanding. Implications of this study include curriculum design, teacher training, and assessment practices that respect the developmental realities of elementary school students.